PRASANGKA: POTENSI PEMICU KONFLIK INTERNAL UMAT ISLAM - Muhammad Alfandi (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2013)
This study is about the potential prejudice sparked internal conflict of Muslims, especially between the group Nahdlatul Ulama (NU) and the Council of Tafsir Al-Qur'an (MTA) in Surakarta. Lately there is a conflict between NU and the MTA congregation. MTA is questioned by NU in some areas because of the materials and methods of preaching/dakwah considered to be provocative and less likely to appreciate the difference fiqhiyah and abusive deeds done by NU. From the reason above, the conflict between these two Islamic organizations appeared. One of the triggers that caused the internal conflict among Muslims is the certain group of Muslims can not understand well the other religious groups, which have different ideological backgrounds; that it affects the way of thinking, behaving and acting that are different from themselves. As a result, the internal relations marred by religious conflict, caused by the internal religious prejudice. Similarly, the possibility that occurred among the group of NU and MTA.